EFFECT OF DIETARY LEVELS OF PROTEIN ON MILK PRODUCTION, MILK-UREA AND NITROGEN USE EFFECIENCY IN PERI-URBAN MILKING BUFFALOES - G. Habib; A. Hameed; M. Saleem (Journal of Animal and Plant Sciences, 2019)
In Pakistan peri-urban milking buffaloes are usually overfed protein in attempt to maximize milk production which adds to the cost of feeding with little or no positive response on performance of the buffaloes. The present study was performed to assess protein status and N use efficiency in peri-urban milking buffaloes maintained on conventional feeding system. One hundred and twentysix (126) buffaloes in early to mid-lactation were selected from 20 peri-urban dairy farms at three different locations in KP province, Pakistan. The farms were visited monthly and data on daily milk yield and feed intake were recorded from January to December 2008.  Samples of feed offered and evening milk were collected for laboratory analysis. The data were analyzed using ANOVA according to RCB factorial design. The results were grouped on the basis of crude protein (CP) in total DM consumed as low CP (9-11%), medium CP (12-14%) and high CP (15-17%). CP levels did not influence DM intake (14.34±0.6 kg) or milk yield (9.13 ± 1.3 liter). Milk urea-N (MUN) linearly (r2 =0.42) increased with increasing CP in the diet and ranged from 11.79 to 17.07 mg/100 ml. Nitrogen use efficiency for milk (MNE) ranged from 14.39% to 22.69% and negatively correlated (r2=0.56) with CP intake. Majority of the buffalos (48%) had CP intake in excess of requirements associated with increase in protein-energy ratios and N loss in excreta. Feed conversion efficiency was not influenced by dietary CP and averaged 0.83±0.12. Excess CP intake resulted from berseem feeding which adversely affected performance of the buffalos. Lower CP intake with feeding of maize fodder supported higher milk yield, improved MNE and reduced MUN. The results concluded that CP intake was influenced by type of fodder and CP higher than 11% in DM did not increase daily milk yield while significantly reduced MNE. Nitrogen utilization for enhanced milk yield in peri-urban buffaloes can be improved by balancing protein-energy ratio of dairy rations.
Keywords: Buffalo; milk production; Milk Urea-N; Nitrogen utilization